1996
DOI: 10.2519/jospt.1996.23.1.39
|View full text |Cite
|
Sign up to set email alerts
|

The Lennie Test for Measuring Scapular Position in Healthy Young Adult Females: A Reliability and Validity Study

Abstract: A search of the literature suggests that normal scapular rest position is neither agreed upon nor entirely described. A~~thoritic-s differ in their anatomical representation (1 ,.5,8,9, 1 1-1 4.17) and written description (9,ll-13) of normal scapular rest position. Kendall et a1 (12) make the distinction that normal scapular rest position is influenced by hand dominance, with the dominant hand having the lower scapula. They, as well as Netter (14). describe the medial borders of the scapulae as being essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 9 publications
(9 reference statements)
7
56
0
2
Order By: Relevance
“…14 In addition, Magee 14 noted that upon relaxation of the upper extremity musculature, as in LSST position 1, the distance between the spinous process and the medial border of the scapula is widened on the dominant side. These findings are also supported by the work of Sobush et al, 21 who suggest a slightly more medial and cranial location of the nondominant scapula, although no statistically significant differences were found between the position of the dominant and nondominant scapula. 21 The current investigation found a significant difference in scapular asymmetry between sex in positions 2 and 3, with males demonstrating greater asymmetry than females.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…14 In addition, Magee 14 noted that upon relaxation of the upper extremity musculature, as in LSST position 1, the distance between the spinous process and the medial border of the scapula is widened on the dominant side. These findings are also supported by the work of Sobush et al, 21 who suggest a slightly more medial and cranial location of the nondominant scapula, although no statistically significant differences were found between the position of the dominant and nondominant scapula. 21 The current investigation found a significant difference in scapular asymmetry between sex in positions 2 and 3, with males demonstrating greater asymmetry than females.…”
Section: Discussionsupporting
confidence: 81%
“…These findings are also supported by the work of Sobush et al, 21 who suggest a slightly more medial and cranial location of the nondominant scapula, although no statistically significant differences were found between the position of the dominant and nondominant scapula. 21 The current investigation found a significant difference in scapular asymmetry between sex in positions 2 and 3, with males demonstrating greater asymmetry than females. A number of studies report that males have a greater percentage of muscle mass to total body weight than females, and that males have greater muscle cross-sectional area than females, with a greater difference between sex in the upper extremities compared to the lower extremities.…”
Section: Discussionsupporting
confidence: 81%
“…28 31 to reliably measure position of the scapulae in three dimensions to determine whether the di erences in postural control, shown to be signi®cant in the sample population, could be reproduced more accurately in another sample. This would have allowed for the results to be applied more broadly within paraplegia.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this cadaveric study showed that the difference between surface locations and bony locations confirmed with tissue resection (gold standard) of the acromion angle and thoracic spinous processes was less than 0.98 and 1.46 cm, respectively. Sobush et al 28 found that surface landmark measurements for scapular position were on average within 0.56 cm and within 1.7° of the measurements made from radiographs for linear and angular position, respectively. Billis et al 2 have shown good within-therapist reliability for locating the spinous processes of the cervical and thoracic spine (C5 and T6).…”
Section: Methods and Measuresmentioning
confidence: 99%